2007
DOI: 10.1021/bm061029j
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Complexes between (Cross-linked) N-Carboxyethylchitosan and (Quaternized) Poly[2-(dimethylamino)ethyl methacrylate]:  Preparation, Characterization, and Antibacterial Properties

Abstract: Novel polyelectrolyte complexes (PECs) between N-carboxyethylchitosan (CECh) and well-defined (quaternized) poly[2-(dimethylamino)ethyl methacrylate] (PDMAEMA) have been obtained. The modification of chitosan into CECh allows the preparation of PECs in a pH range in which chitosan cannot form complexes. The CECh/PDMAEMA complex is formed in a narrow pH range around 7. The quaternization of the tertiary amino groups of PDMAEMA enables complex formation with CECh both in neutral and in alkaline medium. Cross-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 24 publications
5
99
0
1
Order By: Relevance
“…While it is possible that the quaternised polymer is able to inhibit growth of Gram-negative bacteria over short periods, over longer periods the bacteria are able to grow back. In addition, Yancheva et al 33 found that unconjugated and 50 % quaternised pDMAEMA had a similar inhibitory effect against E. coli, producing an MIC of 0.3 mg/ml. This value is similar to the MIC we found for the unconjugated polymer against E. coli ATCC 10536 (0.5 mg/ml).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is possible that the quaternised polymer is able to inhibit growth of Gram-negative bacteria over short periods, over longer periods the bacteria are able to grow back. In addition, Yancheva et al 33 found that unconjugated and 50 % quaternised pDMAEMA had a similar inhibitory effect against E. coli, producing an MIC of 0.3 mg/ml. This value is similar to the MIC we found for the unconjugated polymer against E. coli ATCC 10536 (0.5 mg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, pDMAEMA has been attached to glass 28,29 , filter paper 28,30 , polystyrene 31 and polypropylene 32 and also as an antimicrobial surface coating to inhibit the growth of Escherichia coli (E. coli) and Bacillus subtilis. It has also been incorporated in antimicrobial copolymers to inhibit growth of E. coli 33 and S. aureus 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic star copolymers composed of poly(2-dimethylaminoethyl methacrylate)-block-poly(n-butyl acrylate) (PDMAEMA-b-PBA) arms covalently linked to a β-CD core are especially interesting, because they can be used in biomedical applications, including drug delivery and tissue engineering. PDMAEMA is the most extensively studied pH-responsive polymer [45][46][47][48][49][50], because it is able to function as the pH-responsive component as it has a nitrogen moiety, which can be protonated by lowering the pH of the solution [48,49], and shows pH-dependent lower critical solution temperature behavior [45] and upper critical solution temperature behavior at low temperatures in the presence of multivalent counter ions [47]. Furthermore PBA is an industrially important polymer because of its low glass-transition temperature, durability, and potential use as a soft segment in thermoplastic elastomers [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Yine amino grubu sayısını arttırmak için N-ucuna asparajin aminoasidi eklenmiş kitosan oligosakkaritlerinin, bakteri hücre duvarındaki negatif yüklü karboksil gruplarıyla daha kuvvetli etkileşime girdikleri saptanmıştır [31]. Tersine, amino grubuna etil karboksil eklenmiş kitosanın (N-karboksi etil kitosan) antibakteriyel aktivitesini tamamen yitirdiği belirlenmiştir [32].…”
Section: Antibakteriyel Mekanizmaunclassified